Vascularization approaches in tissue engineering: recent developments on evaluation tests and modulation - Lopes, Soraia V. (2021)
This review focuses on vascularization and strategies involved in its evaluation and modulation. Clinical issues associated with engineered tissues of an atomically relevant size that require a vascular network to supply their cells with nutrients and oxygen are analyzed in terms of vascular network formation within scaffolds, which can be produced from varying biomaterials, with the capability of connecting to the vasculature of the patient. Developing angiogenesis techniques and monitoring of angiogenesis development as well as how these methods can be further utilized to tailor vascularization within large tissue engineered constructs are also discussed. Finally, we offer a glimpse toward the future by providing an outlook for vascularization and associated emerging bioprinting concepts in tissue engineering applications.